An Investigation into Different Forms of Persian Lexical Borrowing from French, Causes, and Pathology - Fahandej Saadi, Rahim (LANGUAGE ART, 2020)
The Persian language has long been a source of many words from different Eastern and Western languages. One of the languages that has sent many words to Persian, especially in the last century and a half is French. In some cases, these borrowings have met the needs of the Persian language, but also in some others, not only have they not filled language gaps, but they have caused linguistic and cultural damage, too. In addition to examining different ways in which the Persian language borrows from French (complete borrowing, hybridism, composed-hybridism, false friends, and loan translation), this study discusses the necessity and non-necessity of borrowing. The results of this survey and the analysis of extracted data ultimately lead to the presentation of four principles for borrowing to minimize the entry of inefficient words into the Persian language.